Mechanical performance of fibre reinforced polymer (FRP) composite - Cheong, Yong Xiang (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Composite material is a major technological advancement in the field of material sciences. Composites are applied in many major aspects of engineering, for example automotive, construction, aerospace and many more. Fibre Reinforced Polymer (FRP) is a composite material that utilizes a polymer as a matrix and high strength fibre as reinforcement. Polymer alone do not have the desired properties therefore fibre reinforcement are added to enhance its mechanical performance. FRP composite is known for its superior mechanical properties such as tensile strength, flexural strength and more. Therefore, FRP composite is very popular in the manufacturing industry.